Single Nucleotide Polymorphisms in Apolipoprotein B, Apolipoprotein E, and Methylenetetrahydrofolate Reductase Are Associated With Serum Lipid Levels in Northern Chilean Subjects. A Pilot Study - Gálvez, Anita S.; Ramírez, Hugo; Placencia, Pablo; Rojas, Claudio; Urzúa, Ximena; Kalergis, Alexis M.; Salazar, Luis A.; Escobar-Vera, Jorge (Frontiers in Genetics, 2021)
Characterization of genetic variants are relevant to establish relationships between genetic background and susceptibility to develop cardiovascular diseases (CVD), which are the main cause of death in Chile. APOB, APOE and MTHFR polymorphisms have been associated with higher lipid levels and the risk of developing hypertension and cardiovascular diseases. Thus, the main goal of this study was to evaluate genotype distribution and relative allelic frequency of ApoB rs693, ApoE rs7412/rs429358 and MTHFR rs1801131 and rs1801133 genetic variants and their effects on lipid levels in young healthy individuals from Northern Chile. A total of 193 healthy individuals were recruited for this study. Genotyping of rs693 (APOB), rs7412 and rs429358 (APOE), rs1801131 and rs1801133 (MTHFR) polymorphisms were performed by real time PCR, in addition, glucose and lipid levels were determined and associated with the genetic data. The genotype distribution was: APOB rs693 (CC=37%; CT=41% and TT=22%), APOE rs7412/rs429358 (E4=0.06; E3=0.91 and E2=0.03), MTHFR rs1801131 (AA=57%; AC=30% and CC=13%) and MTHFR rs1801133 (CC=20%; CT=47% and TT=33%). The association of the genetic variants with plasma lipid levels showed that women, but not men, carrying APOB mutated allele (T) as well as Apo E4 allele presented lower values of total cholesterol when compared to C/C homozygous genotype or E3 allele respectively (p<0.05). In addition, a subgroup analysis revealed that C/C homozygous women exhibited higher values of HDL-C when compared to male group carrying the same genotype (p<0.01). On the other hand, women carrying E4 allele exhibited lower values of triglycerides when compared to male group carrying the same genotype (p<0.05). Finally, women carrying mutate alelle (C) for MTHFR rs1801131 showed lower levels of triglycerides when compared to A/A homozygous genotype (p<0.05) and lower levels of LDL-C for MTHFR rs1801133 in female carrying (T) allele when compared to male group carrying the same genotype (p<0.05). In summary, the present data showed that APOB, APOE and MTHFR single nucleotide polymorphisms are associated to lipid levels in a gender-dependent manner among healthy subjects from Northern Chile, especially in women.